Single-phase current-source-boost inverter for renewable energy sources - Sampaio, Leonardo P. [UNESP]; De Brito, Moacyr A.G. [UNESP]; Junior, Luigi G. [UNESP]; De A. E Melo, Guilherme [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a new methodology for the operation and control of a single-phase current-source (CS) Boost Inverter, considering that the conventional CS boost inverter has a right-half-plane (RHP) zero in its control-to-output transfer function, and this RHP zero causes the known non-minimum-phase effects. In this context, a special design with low boost inductance and a multi-loop control is developed in order to assure stable and very fast dynamics. Furthermore, the proposed inverter presents output voltage with very low total harmonic distortion (THD), reduced components and high power density. Therefore, this paper presents the inverter operation, the proposed control technique, the main simulation results and a prototype in order to demonstrate the feasibility of the proposal. © 2011 IEEE.
Keywords: Boost inverters; Control techniques; Current sources; Fast dynamics; High power density; Inverter operations; Multi-loop control; Non-minimum phase; Operation and control; Output voltages; Renewable energy source; Right half plane zero; Total harmonic distortions; Renewable energy resources; Industrial electronics